A composite lithium iron phosphate positive electrode material and its preparation method and application
Through the preparation method of composite lithium iron phosphate positive electrode material, combined with the granulation and compounding process of ferrous phosphide and carbon source, the problems of low energy density and complex negative electrode lithium supplementation process of lithium iron phosphate lithium ion batteries are solved, and the effects of high energy density, excellent low temperature performance and simple process are achieved.
Patent Information
- Application Number
- CN202211611246.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The existing lithium iron phosphate lithium-ion batteries have low energy density and cannot meet the long-term battery life demand of the mid-to-high-end power vehicle market. The negative electrode lithium supplementation process poses safety risks and complex processing technology problems.
Using the preparation method of composite lithium iron phosphate positive electrode material, the composite lithium iron phosphate positive electrode material is mixed with ferrous phosphate powder to form precursor A, and the lithium iron phosphate powder to form carbon source to form precursor B, and finally compound and calcined to prepare composite lithium iron phosphate positive electrode material.
It improves the energy density and material stability of lithium-ion batteries, has excellent low-temperature magnification performance, simple process, low production cost, and is suitable for industrial production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries are increasingly used in power vehicles, and the performance requirements of batteries are also increasing. The promotion and large-scale application of power batteries require lithium-ion batteries with better safety and performance. Compared with the short life of lead-acid batteries, the safety defects and high cost of ternary lithium-ion batteries are difficult to solve. Lithium iron phosphate lithium-ion batteries, which have relatively compromised or even advantageous performance in all aspects, are more advantageous.
[0003] Lithium iron phosphate (LFP) lithium-ion batteries also have relatively obvious disadvantages, especially the low high energy density. The energy density of a general single cell is only about 170Wh / kg, which cannot meet the long-range requirements of the mid-to-high-end power vehicle market. At present, pre-lithiation technology is mostly used to improve the energy density of lithium iron phosphate batteries. Selecting a suitable lithium supplement can increase the energy density of lithium iron phosphate cells to 180Wh / kg or even 190Wh / kg. Pre-lithiation technology is mainly divided into positive electrode lithium supplementation and negative electrode lithium supplementation. There are greater safety risks and complex and difficult processing technology problems in negative electrode lithium supplementation. Compared with negative electrode lithium supplementation, the positive electrode lithium supplementation process is simple. The lithium source is added through the positive electrode slurry process, which can completely avoid the safety risks and cost increase risks of negative electrode lithium supplementation. The positive electrode lithium supplementation process is to add a small amount of high-capacity lithium supplementation additives to the positive electrode during the homogenization of the positive electrode. During the charging process, the excess Li element is removed from these high-capacity positive electrode materials and embedded in the negative electrode to supplement the irreversible capacity of the first charge and discharge.
[0004] CN108878849A only uses organic carbon coating, which can effectively isolate Li5FeO4 from water and carbon dioxide in the air to a certain extent, but the coating uniformity is general. The Li5FeO4 / C material prepared by it has a high residual alkali content. When added to the positive electrode material for homogenization, it is still easy to cause the slurry to gel, which may lead to the inability to coat.
[0005] CN114560505A first nano-sizes the precursor of Li5FeO4 and then coats the surface with amorphous carbon. The surface coating with the amorphous carbon layer increases the conductivity and acts as a conductive agent after lithium supplementation to reduce the internal resistance of the battery. However, the particle size of the Li5FeO4 particles synthesized by this method is less than 50nm. The particle size is too small and it is easy to absorb water and produce side reactions during homogenization, and the slurry is more likely to gel. Summary of the invention
[0006] The object of the present invention is to provide a composite lithium iron phosphate positive electrode material and a preparation method and application thereof. The composite lithium iron phosphate positive electrode material of the present invention has a high compaction density of the electrode sheet, excellent rate performance under low temperature conditions, and effectively improves the LFP capacity while improving the material stability. The preparation method is simple, the production cost is low, and it is energy-saving and efficient, so it is suitable for industrial production.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a composite lithium iron phosphate positive electrode material, the preparation method comprising the following steps:
[0009] (1) mixing lithium ferrite powder and ferrous phosphide, performing a granulation process to obtain first particles, and performing a one-step calcination process to obtain a precursor A;
[0010] (2) mixing the lithium iron phosphate powder and the carbon source and performing a secondary granulation process to obtain second particles, and performing a two-step calcination process to obtain a precursor B;
[0011] (3) Precursor A and precursor B are compounded and calcined to obtain the composite lithium iron phosphate positive electrode material.
[0012] The present invention adopts an organic combination of multiple improvement methods rather than a simple superposition. In the preparation process of the composite lithium iron phosphate positive electrode material described in the present invention, a precursor A containing ferrous phosphide and a precursor B containing a carbon coating layer are prepared in advance, and then the two are compounded to form a composite lithium iron phosphate positive electrode material. Ferrous phosphide has strong conductivity, which can effectively solve the problem of poor conductivity of lithium ferrite, and is conducive to lithium removal of lithium ferrite at a large rate; finally, carbon coating can effectively alleviate the gel problem of lithium supplement materials during homogenization due to strong residual alkalinity; at the same time, lithium ferrite and lithium iron phosphate complement each other and progress step by step, which not only solves the problem of poor conductivity and unstable material of lithium ferrite material itself, but also ensures the capacity of lithium iron phosphate while improving the low temperature performance of the material.
[0013] Preferably, the median particle size D50 of the lithium ferrite in step (1) is 0.1-0.2 μm, for example, 0.1 μm, 0.15 μm, 0.2 μm, etc.
[0014] Preferably, in step (1), the median particle size D50 of the first particles is 2 to 4 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm.
[0015] Preferably, D90 of the first particles is ≤10 μm.
[0016] Preferably, the mass ratio of the lithium ferrite powder to ferrous phosphide in step (1) is 100:(0.1-1.0), for example: 100:0.1, 100:0.2, 100:0.5, 100:0.8 or 100:1.0, etc.
[0017] Preferably, the temperature of the one-step calcination treatment is 200-400°C, for example, 200°C, 250°C, 300°C, 350°C or 400°C.
[0018] Preferably, the mass ratio of the lithium iron phosphate powder and the carbon source in step (2) is 100:(1-2), for example: 100:1, 100:1.2, 100:1.5, 100:1.8 or 100:2, etc.
[0019] Preferably, the carbon source comprises any one of glucose, sucrose, fructose, polypyrrole, polypyridine or polythiophene, or a combination of at least two thereof.
[0020] Preferably, the median particle size D50 of the second particles is 0.5-3.0 μm, for example, 0.5 μm, 1.0 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0021] Preferably, D90 of the second particles is ≤15 μm.
[0022] Preferably, the temperature of the two-step calcination treatment is 200-400°C, for example, 200°C, 250°C, 300°C, 350°C or 400°C.
[0023] Preferably, the compounding ratio of the precursor A and the precursor B in step (3) is (1-5):100, for example: 1:100, 2:100, 3:100, 4:100 or 5:100, etc.
[0024] Preferably, the carbon source comprises any one of glucose, sucrose, fructose, polypyrrole, polypyridine or polythiophene, or a combination of at least two thereof.
[0025] Preferably, the mass ratio of the total mass of the precursor A and the precursor B to the carbon source is 100:(1-2), for example: 100:1, 100:1.2, 100:1.5, 100:1.8 or 100:2, etc.
[0026] Preferably, the temperature of the calcination treatment in step (3) is 500-800°C, for example, 500°C, 550°C, 600°C, 700°C or 800°C.
[0027] Preferably, the calcination treatment time is 10 to 18 hours, for example: 10 hours, 12 hours, 14 hours, 16 hours or 18 hours.
[0028] In a second aspect, the present invention provides a composite lithium iron phosphate positive electrode material, which is prepared by the method described in the first aspect.
[0029] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the composite lithium iron phosphate positive electrode material as described in the second aspect.
[0030] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The electrode sheet made of the composite lithium iron phosphate positive electrode material of the present invention has a high compaction density and excellent rate performance under low temperature conditions. While effectively improving the capacity of LFP, the material stability is improved. The preparation method and process are relatively simple, the production cost is low, and it is energy-saving and efficient, which is suitable for industrial production.
[0033] (2) The composite lithium iron phosphate positive electrode material of the present invention adopts the method of regulating the particle size distribution to reduce the unit active sites of the lithium supplement agent, thereby delaying the reaction of residual alkali with CO2 and water in the air, thereby slowing down the time of gel formation during homogenization, and can meet the requirement of 18h gel-free slurry. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0035] Example 1
[0036] This embodiment provides a composite lithium iron phosphate positive electrode material, and the preparation method of the composite lithium iron phosphate positive electrode material is as follows:
[0037] (1) mixing lithium ferrite powder with a D50 of 0.15 μm and pure Fe2P powder in a mass ratio of 100:0.5, stirring and sand-milling, granulating to a D50 of 2 μm, and then calcining at 300° C. to obtain precursor A;
[0038] (2) lithium iron phosphate powder with a D50 of 0.2 μm and glucose were mixed in a mass ratio of 100:1.2 and then granulated for a second time, with a D50 particle size of 2 μm, and then calcined at 350° C. to obtain precursor B;
[0039] (3) Precursor A and precursor B are compounded in a ratio of 3:100, glucose (1.5% of the total mass of precursor A and precursor B) is added, stirred thoroughly, dried, placed in a nitrogen atmosphere furnace, heated at a rate of 5°C / min, calcined at a constant temperature of 650°C for 10 hours, and finally cooled to room temperature to obtain the composite lithium iron phosphate positive electrode material.
[0040] Example 2
[0041] This embodiment provides a composite lithium iron phosphate positive electrode material, and the preparation method of the composite lithium iron phosphate positive electrode material is as follows:
[0042] (1) mixing lithium ferrite powder with a D50 of 0.20 μm and pure Fe2P powder in a mass ratio of 100:1, stirring and sand-milling, granulating to a D50 of 4 μm, and then calcining at 320° C. to obtain precursor A;
[0043] (2) lithium iron phosphate powder with a D50 of 0.15 μm and glucose were mixed in a mass ratio of 100:1 and then granulated for a second time, with a D50 particle size of 3 μm, and then calcined at 350° C. to obtain precursor B;
[0044] (3) Precursor A and precursor B are compounded in a ratio of 1:100, glucose (1.5% of the total mass of precursor A and precursor B) is added, stirred thoroughly, dried, placed in a nitrogen atmosphere furnace, heated at a rate of 5°C / min, calcined at a constant temperature of 680°C for 9h, and finally cooled to room temperature to obtain the composite lithium iron phosphate positive electrode material.
[0045] Example 3
[0046] The only difference between this embodiment and embodiment 1 is that the mass ratio of the lithium ferrite powder to the ferrous phosphide in step (1) is 100:0.05, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0047] Example 4
[0048] The only difference between this embodiment and embodiment 1 is that the mass ratio of the lithium ferrite powder to the ferrous phosphide in step (1) is 100:1.2, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0049] Example 5
[0050] The only difference between this embodiment and embodiment 1 is that the compounding ratio of precursor A and precursor B in step (3) is 0.5:100, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0051] Example 6
[0052] The only difference between this embodiment and embodiment 1 is that the compounding ratio of precursor A and precursor B in step (3) is 6:100, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0053] Comparative Example 1
[0054] The only difference between this comparative example and Example 1 is that ferrous phosphide is not added, and other conditions and parameters are exactly the same as those in Example 1.
[0055] Comparative Example 2
[0056] The only difference between this comparative example and Example 1 is that no carbon source is added, and other conditions and parameters are exactly the same as those in Example 1.
[0057] Performance Test:
[0058] The positive electrode materials obtained in the embodiments and comparative examples are made into slurries, and the viscosity change of the slurries for 24 hours is tested. The lithium iron phosphate positive electrode materials obtained in the embodiments and comparative examples are made into positive electrode plates, which are matched with corresponding graphite negative electrode plates, 12μm PP+PE separators, and 1.0M LiPF6 EC+EMC electrolytes. The separators are between the positive and negative electrodes, and then wound or stacked to obtain bare cells. The bare cells are placed in an outer packaging aluminum plastic film or an aluminum shell to assemble into cells. The electrolyte is injected into the dried cells, and a lithium-ion battery is obtained through aging, formation, shaping, packaging and other processes. The lithium-ion battery is tested for rate discharge at -10°C, 3C and capacity retention at 45°C, 1C for 3000 cycles. The test results are shown in Table 1:
[0059] Table 1
[0060]
[0061] It can be seen from Table 1 that, according to Examples 1-2, increasing Fe2P is beneficial to low-temperature rate performance, and increasing lithium iron phosphate is beneficial to circulation but not to slurry stability.
[0062] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the composite lithium iron phosphate positive electrode material of the present invention, the addition amount of ferrous phosphide in precursor A will affect its performance. If the addition amount of ferrous phosphide is too high, the active ingredients will be reduced; if the addition amount of ferrous phosphide is too low, the conductivity of precursor A cannot be guaranteed, thereby affecting the lithium release capacity of the composite positive electrode material.
[0063] By comparing Example 1 and Examples 5-6, it can be seen that in the composite lithium iron phosphate positive electrode material of the present invention, the compounding ratio of precursor A and precursor B will affect its performance. The performance of the composite lithium iron phosphate positive electrode material obtained by compounding precursor A and precursor B according to (1-5):100 is better. If the proportion of precursor A is too high, the instability of the slurry increases, and the viscosity of the slurry changes greatly within 24 hours, which is not conducive to coating. If the proportion of precursor A is too low, the active components are limited and the cycle performance of the composite material cannot be guaranteed.
[0064] From the comparison between Example 1 and Comparative Example 1, it can be seen that the addition of ferrous phosphide to the precursor A to prepare the composite lithium iron phosphate positive electrode material in the present invention can effectively improve the low-temperature rate performance of the composite positive electrode material.
[0065] By comparing Example 1 and Comparative Example 2, it can be seen that the addition of a carbon source into the precursor B to prepare a composite lithium iron phosphate positive electrode material can effectively isolate the lithium iron phosphate from the moisture and CO2 reaction gel in the air, thereby causing poor slurry stability.
[0066] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite lithium iron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing lithium ferrite powder and ferrous phosphide in a mass ratio of 100:(0.1-1.0) and performing a primary granulation treatment to obtain first particles with a median particle size D50 of 2-4 μm, and performing a one-step calcination treatment at 200-400° C. to obtain a precursor A; (2) mixing lithium iron phosphate powder and a carbon source and performing a secondary granulation treatment to obtain second particles with a median particle size D50 of 0.5 to 3.0 μm, and performing a two-step calcination treatment at 200 to 400° C. to obtain a precursor B; (3) Precursor A and precursor B are compounded in a ratio of (1-5):100, a carbon source is added, and the mixture is calcined at 500-800° C. for 10-18 hours to obtain the composite lithium iron phosphate positive electrode material.
2. The preparation method according to claim 1, characterized in that The median particle size D50 of the lithium ferrite in step (1) is 0.1 to 0.2 μm.
3. The preparation method according to claim 1, characterized in that: The D90 of the first particles is ≤10 μm.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the lithium iron phosphate powder to the carbon source in step (2) is 100:(1-2).
5. The preparation method according to claim 1, characterized in that: The carbon source in step (2) includes any one of glucose, sucrose, fructose, polypyrrole, polypyridine or polythiophene, or a combination of at least two thereof.
6. The preparation method according to claim 1, characterized in that: The D90 of the second particles is ≤15 μm.
7. The preparation method according to claim 1, characterized in that: The carbon source in step (3) includes any one of glucose, sucrose, fructose, polypyrrole, polypyridine or polythiophene, or a combination of at least two thereof.
8. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the total mass of the precursor A and the precursor B to the mass ratio of the carbon source is 100:(1-2).
9. A composite lithium iron phosphate positive electrode material, characterized in that: The composite lithium iron phosphate positive electrode material is prepared by the method according to any one of claims 1 to 8.
10. A positive electrode sheet, characterized in that: The positive electrode plate comprises the composite lithium iron phosphate positive electrode material as claimed in claim 9.
11. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 10.
Citation Information
Patent Citations
Synthesis process of lithium-rich oxide and lithium ion battery containing lithium-rich oxide
CN108878849A
Graphene composite lithium iron phosphate positive electrode material and preparation method and application thereof
CN107068990A
Graphene nano-ribbon-based lithium iron phosphate composite material and preparation method and application thereof
CN110085809A